Breaking Boundaries: First Report of White-shouldered Starling Sturnia sinensis (Passeriformes: Sturnidae) in Indonesia - Abdul Hakim Syah; Muhammad Iqbal (Lembaga Penelitian, Pengabdian Kepada Masyarakat dan Kepustakaan, 2025)
The White-shouldered Starling Sturnia sinensis, a species commonly found in East Asia and known to winter in Southeast Asia, had not been previously recorded in Indonesia’s avifaunal list. On 26 September 2023, an unusual starling was spotted among a flock of Daurian Starlings Agropsar sturninus near a Buddhist vihara in Tanjungpinang, Bintan Island, Riau Islands Province, Sumatra. The following day, the bird was photographed and documented for closer examination. It was ultimately identified as S. sinensis. This record represents a significant range expansion for the species into Indonesian territory, emphasizing the dynamic nature of avian migration and the critical need for ongoing monitoring to capture such unexpected findings.